Acquisition of Morphological Aspect in English by the Students at SDK Ruteng 1 - Gunas, Tobias; Beda, Raimundus; Perdede, Elvisius (Jurnal Pendidikan dan Kebudayaan Missio, 2025)
This study aims to explore the acquistion of English morphemes in English Foreign Language classroom at elementary school. The investigation is concerned with the identification, description, and interpretation of English morphemes acquired by 30 elementary students at SDK Ruteng I in Langke Rembong district. Therefore, descriptive qualitative research method mixed with quatintative approach were applied. a series of classroom observations, note-taking, and audio-recording were utilized to delve into more naturalistic data relating to form and pattern of morphemes. The data from the transcripts and field-notes were analyzed to capture the forms of morpheme as well as to identify frequency and patterns of English morpheme during the acquisition process in EFL learning context. The results of data analysis were displayed in matrix, table and chart, while conclusion drawing and verification were simultenously conducted at the final procedure. Verification of data was triangulized by comparing the data from recording and field-notes. The findings reveal that free and bound morphemes are acquired differently by students in learning English vocabulary. Free morphemes are predominantly acquired, especially in the categories of nouns and verbs, whereas bound morphemes are less frequently obtained. These findings indicate that the acquisition of morphological aspects follows a sequence, beginning with free morphemes and subsequently progressing to bound morphemes. Among bound morphemes, inflectional morphemes are acquired earlier than derivational morphemes. Based on the findings, it is concluded that the acquisition of morphemes in English is more complex due to different language structures and aligns with the developmental stages of individual learners' linguistic developmen